2020
DOI: 10.1126/science.abd3871
|View full text |Cite
|
Sign up to set email alerts
|

Selective and cross-reactive SARS-CoV-2 T cell epitopes in unexposed humans

Abstract: Many unknowns exist about human immune responses to the SARS-CoV-2 virus. SARS-CoV-2 reactive CD4+ T cells have been reported in unexposed individuals, suggesting pre-existing cross-reactive T cell memory in 20-50% of people. However, the source of those T cells has been speculative. Using human blood samples derived before the SARS-CoV-2 virus was discovered in 2019, we mapped 142 T cell epitopes across the SARS-CoV-2 genome to facilitate precise interrogation of the SARS-CoV-2-specific CD4+ T cell repertoire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

141
1,368
7
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,128 publications
(1,528 citation statements)
references
References 46 publications
141
1,368
7
12
Order By: Relevance
“…The conservation state annotations are complementary to constraint scores, as they capture a more diverse set of evolutionarily patterns of bases aligning and matching, enabling one to group genomic bases by states and study each state's functional relevance. Understanding patterns of conservation across different strains can be important potentially for understanding cross-immunity from other coronaviruses [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The conservation state annotations are complementary to constraint scores, as they capture a more diverse set of evolutionarily patterns of bases aligning and matching, enabling one to group genomic bases by states and study each state's functional relevance. Understanding patterns of conservation across different strains can be important potentially for understanding cross-immunity from other coronaviruses [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are also confident that they have made solid inroads into ascertaining the origins of the immune responses. “Our hypothesis, of course, was that it’s so called ‘common cold’ coronaviruses, because they’re closely related,” said Daniela Weiskopf, senior author of a paper in Science that confirmed this hypothesis 18. “We have really shown that this is a true immune memory and it is derived in part from common cold viruses.” Separately, researchers in Singapore came to similar conclusions about the role of common cold coronaviruses but noted that some of the T cell reactivity may also come from other unknown coronaviruses, even of animal origin 8…”
Section: Not So Novel Coronavirus?mentioning
confidence: 98%
“…Recent studies have shown that many people infected with SARS-CoV-2 virus with mild synptoms or asymptomatic status can develop T-cell-mediated immunity to the virus even without antibody response 24 . In addition, ananlysis of T cell immunity to speci c SARS-CoV-2 epitopes also demonstrates the existence of anti-viral T cells in un-exposed individuals [25][26][27] . This means that the actual level of population immunity to the new coronavirus is higher than the antibody positive population.…”
Section: Discussionmentioning
confidence: 95%